2020
DOI: 10.3311/ppci.16030
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Mechanical Cumulative Damage Model of Slope Fault Fracture Zone under the Cumulative Effect of Blasting Vibration

Abstract: As for the slope with fault fracture zone, the fault fracture zone is the main sliding surface, whose shear strength parameter is the main calculation parameter of landslide occurrence. In this paper, shaking table model tests and damage theory were used to study the change of shear strength and mechanical cumulative damage model of fault fracture zone under the blasting vibration cyclic load. At first, the slope of Daye Iron Mine is selected as a case to study the shear strength weakening law of fault fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Whether it is natural landscape or cultural landscape, what it contains is the diversity of regional landscape. However, different people or groups may perceive and describe the same landscape completely differently, so it is a common study among Western scholars that the settlement landscape is conceived or "invented" by the perceiver, and the landscape is endowed with rich diversity and meaning in the process of being perceived, described, and displayed [12].…”
Section: Related Studiesmentioning
confidence: 99%
“…Whether it is natural landscape or cultural landscape, what it contains is the diversity of regional landscape. However, different people or groups may perceive and describe the same landscape completely differently, so it is a common study among Western scholars that the settlement landscape is conceived or "invented" by the perceiver, and the landscape is endowed with rich diversity and meaning in the process of being perceived, described, and displayed [12].…”
Section: Related Studiesmentioning
confidence: 99%
“…Besides, as digital tools are becoming increasingly closely integrated with the practice and research of landscape disciplines, this paper hopes to enrich its research content from the side of landscape patterns and deepen the research connotation of digital landscape studies. e study and analysis of landscape patterns used to play a pivotal role in urban site selection, residence phasing, and garden creation, while the current planning and design of cities and landscapes are paying increased attention to ecological sustainability and local characteristics [2]. is paper constructs a framework for digital analysis of multiscale landscape patterns to provide a certain degree of reference for how to conduct systematic analysis and how landscape patterns can provide support and strategies for subsequent planning and design [3].…”
Section: Introductionmentioning
confidence: 99%
“…Combining the above two equations gives the area of the collapse area (shaded part in the Figure 3a) as follows S m = S t − S h − S 1 (14) The height of the accumulation body in the fault fracture zone is discussed as follows:…”
Section: Height Of the Collapse Accumulation Bodymentioning
confidence: 99%
“…Reference [13], by comparing the deformation within the fault transfer zone, concluded that the fluid flow and permeability may be significantly enhanced when the fracture intensity is higher. In reference [14], a theoretical model was proposed to predict the degradation trend of shear strength of the fault fracture zone under cyclic dynamic and static loads. Reference [15] analyzed the collapse characteristics of a mining roadway in the fault fracture zone after a gas explosion, which was of guide value for the rescue work.…”
Section: Introductionmentioning
confidence: 99%